Biochemistry of Autoinflammatory Diseases: Catalyzing Monogenic Disease - Beck, David B.; Aksentijevich, Ivona (Frontiers in Immunology, 2019)
Monogenic autoinflammatory disorders are a group of conditions defined by systemic or localized inflammation without identifiable causes, such as infection. In contrast to classical primary immunodeficiencies that manifest with impaired immune responses, these disorders are due to defects in genes that regulate innate immune responses leading to constitutive activation of pro-inflammatory signaling. Through studying patients with rare autoinflammatory conditions, novel mechanisms of inflammation have been identified that bare on our understanding not only of basic signaling in inflammatory cells, but also of the pathogenesis of more common inflammatory diseases and have guided treatment modalities. Autoinflammation has further been implicated as an important component of cardiovascular, neurodegenerative, and metabolic syndromes. In this review, we will focus on a subset of inherited enzymatic deficiencies that lead to constitutive inflammation, and how these rare diseases have provided insights into diverse areas of cell biology not restricted to immune cells. In this way, Mendelian disorders of the innate immune system, and in particular loss of catalytic activity of enzymes in distinct pathways, have expanded our understanding of the interplay between many seemingly disparate cellular processes. We also explore the overlap between autoinflammation, autoimmunity and immunodeficiency, which has been increasingly recognized in patients with dysregulated immune responses.